A STUDY ON THE SHARES OF SEVERAL INDEPENDENT VARIABLES IN PREDICTING THE DOMESTIC GAS PRICE - Andry Prima (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2016)
End users of natural gas have long waited for the government regulation on a more rational gas price. In 2017, the answer to the end users is the new Energy and Mineral Resources Ministerial Decree number 434 K/12/MEM/2017 on the supervision of energy business activities, one of which is the natural gas sector. Prior to the stipulation, the price of natural could reach over 12 / MM BTU. Thus, the decree stipulates the price of natural gas should be 9,95 / MMBTU. This paper aims at capturing the closer profiles of variables that might have profound impact on the price of domestic natural gas. Analytical Data Tools used in this study are the IBM – SPSS and XLSTAT In the end, the study resulting the price range suggestion, that is in still in line with the government suggested price